Answer:
.006702
Step-by-step explanation:
Answer:
hmm. 15 - 12 =3
Step-by-step explanation:
correct ba sorry grade 4 palang bobo pa
Answer:
What are you supposed to do
Step-by-step explanation:
First, rearrange the equation so that it is solving for y:
3x - y = 1
+y +y
3x = y + 1
-1 -1
3x - 1 = y
Now substitute the domain values you have listed into the 'x' of the equation to get the values for y.
For example:
3(-3) - 1 = y
-9 - 1 = y
y = -10
-44 because if u multiply -11 by 4 you get -44 and when divided by 4 you get -11